Manajemen Pendidikan Islam: MODEL PERENCANAAN PROGRAM TAHFIDZ AL-QUR’AN UNTUK MEMPERCEPAT PENCAPAIAN TARGET HAFALAN DI PESANTREN PUTRI WAHDATUT TAUHID - Deuis Aisah (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
Preserving the Qur'an through tahfidz learning requires a structured system to ensure memorization quality and character development. However, previous studies have focused on memorization outcomes rather than examining the implementation process comprehensively. This study aims to analyze the implementation of Tahfidz Al-Qur'an learning and identify its supporting factors at Pondok Pesantren Wahdatut Tauhid, Kabupaten Bandung. A descriptive quantitative method was employed, involving four instructors and thirty students. Data were collected through structured observation, semi-structured interviews, and documentation, then analyzed using percentage-based descriptive analysis. The findings indicate that the implementation is categorized as very good, achieving 85.20% within the 81-100% range. The effectiveness is supported by students' learning motivation, instructor competence, a structured memorization system, a conducive boarding school environment, and adequate facilities. These findings confirm that the success of tahfidz is determined by systemic interaction between internal and external factors, not by a single factor. This study provides empirical evidence on institutional-based tahfidz learning implementation and identifies key supporting factors for improving tahfidz program management in Islamic boarding schools.